Hubungan Antara Kadar Vitamin D25 (OH) Dengan Kreatinin Serum Pada Pasien Gagal Ginjal Kronik Stadium Awal - Apriani (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Low levels of vitamin D in the body are known to be involved in the development of kidney disease and proteinuria. Serum creatinine is the most common serum marker for kidney function. Serum creatinine levels will increase in people with chronic kidney failure. The study aimed to look at the association of vitamin D 25 (OH) levels and serum creatinine levels in early-stage chronic kidney failure patients. The research design used is correlation research design. Sampling and examination was conducted at Siloam Hospitals Lippo Village Tangerang. The sampling technique used in this study is purposive sampling. Sample examination using Cobas 6000 Analyzer Series. The results of examination of vitamin D 25 (OH) levels of 85 respondents were known to have normal vitamin D 25 (OH) levels (71%), insufficiency (21%) and deficiency (8%). The results of the statistical analysis showed the value of r = 0.024403555 and P value = 0.153378052, meaning that no association between vitamin D 25 (OH) levels and serum creatinine in people with early stage chronic kidney failure and H0 was accepted